Development of Magnetic Nanoparticles from Poplar Sawdust for Removal of Pesticides from Aqueous Solution - Nayak, Arunima; Bhushan, Brij; Sharma, Pradeep Kumar; Gupta, Vartika (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*337.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01962);" role="presentation">A m<span dir="ltr" style="left: calc(var(–scale-factor)*90.02px); top: calc(var(–scale-factor)*337.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898757);" role="presentation">agnetic nano-<span dir="ltr" style="left: calc(var(–scale-factor)*144.74px); top: calc(var(–scale-factor)*337.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.876867);" role="presentation">adsorbent <span dir="ltr" style="left: calc(var(–scale-factor)*186.77px); top: calc(var(–scale-factor)*337.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977509);" role="presentation">from <span dir="ltr" style="left: calc(var(–scale-factor)*209.33px); top: calc(var(–scale-factor)*337.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945139);" role="presentation">widely available agricultural waste by-<span dir="ltr" style="left: calc(var(–scale-factor)*367.03px); top: calc(var(–scale-factor)*337.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94751);" role="presentation">product viz. <span dir="ltr" style="left: calc(var(–scale-factor)*418.54px); top: calc(var(–scale-factor)*337.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907103);" role="presentation">poplar sawdust <span dir="ltr" style="left: calc(var(–scale-factor)*482.50px); top: calc(var(–scale-factor)*337.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964437);" role="presentation">(MNPSD) <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.875648);" role="presentation">was <span dir="ltr" style="left: calc(var(–scale-factor)*90.02px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.896235);" role="presentation">successfully prepared <span dir="ltr" style="left: calc(var(–scale-factor)*179.09px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943028);" role="presentation">by applying <span dir="ltr" style="left: calc(var(–scale-factor)*229.13px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918956);" role="presentation">chemical <span dir="ltr" style="left: calc(var(–scale-factor)*267.77px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895441);" role="presentation">co-<span dir="ltr" style="left: calc(var(–scale-factor)*280.49px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925389);" role="presentation">precipitation method <span dir="ltr" style="left: calc(var(–scale-factor)*366.19px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869552);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*383.35px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.868337);" role="presentation">was <span dir="ltr" style="left: calc(var(–scale-factor)*401.35px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889783);" role="presentation">subsequently <span dir="ltr" style="left: calc(var(–scale-factor)*456.10px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.889072);" role="presentation">characterized <span dir="ltr" style="left: calc(var(–scale-factor)*512.02px); top: calc(var(–scale-factor)*350.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*363.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.994095);" role="presentation">its unique properties of high surface area and nano-<span dir="ltr" style="left: calc(var(–scale-factor)*299.11px); top: calc(var(–scale-factor)*363.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950326);" role="presentation">size particles. A<span dir="ltr" style="left: calc(var(–scale-factor)*368.71px); top: calc(var(–scale-factor)*363.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951118);" role="presentation">dsorption stud<span dir="ltr" style="left: calc(var(–scale-factor)*428.38px); top: calc(var(–scale-factor)*363.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962702);" role="presentation">ies were <span dir="ltr" style="left: calc(var(–scale-factor)*469.42px); top: calc(var(–scale-factor)*363.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.890485);" role="presentation">conducted <span dir="ltr" style="left: calc(var(–scale-factor)*515.74px); top: calc(var(–scale-factor)*363.53px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999855);" role="presentation">in <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*376.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910296);" role="presentation">laboratory batch mode <span dir="ltr" style="left: calc(var(–scale-factor)*165.14px); top: calc(var(–scale-factor)*376.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.897504);" role="presentation">to evaluate <span dir="ltr" style="left: calc(var(–scale-factor)*211.73px); top: calc(var(–scale-factor)*376.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945);" role="presentation">its <span dir="ltr" style="left: calc(var(–scale-factor)*223.85px); top: calc(var(–scale-factor)*376.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91571);" role="presentation">capacity to remove <span dir="ltr" style="left: calc(var(–scale-factor)*303.43px); top: calc(var(–scale-factor)*376.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921772);" role="presentation">methoxychlor and <span dir="ltr" style="left: calc(var(–scale-factor)*378.91px); top: calc(var(–scale-factor)*376.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917069);" role="presentation">methyl<span dir="ltr" style="left: calc(var(–scale-factor)*406.51px); top: calc(var(–scale-factor)*376.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910403);" role="presentation">parathion. <span dir="ltr" style="left: calc(var(–scale-factor)*449.62px); top: calc(var(–scale-factor)*376.73px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936846);" role="presentation">Methoxychlor and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*389.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922649);" role="presentation">methylparathion <span dir="ltr" style="left: calc(var(–scale-factor)*140.06px); top: calc(var(–scale-factor)*389.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903479);" role="presentation">are organic based pollu<span dir="ltr" style="left: calc(var(–scale-factor)*233.69px); top: calc(var(–scale-factor)*389.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893439);" role="presentation">tants that are detected in the wastewaters due to their excessive usage in <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*403.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92607);" role="presentation">agriculture. <span dir="ltr" style="left: calc(var(–scale-factor)*120.74px); top: calc(var(–scale-factor)*403.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951576);" role="presentation">The maximum adsorption efficiency of MNPSD for methoxychlor <span dir="ltr" style="left: calc(var(–scale-factor)*393.19px); top: calc(var(–scale-factor)*403.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*410.59px); top: calc(var(–scale-factor)*403.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892859);" role="presentation">atrazine <span dir="ltr" style="left: calc(var(–scale-factor)*445.42px); top: calc(var(–scale-factor)*403.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905528);" role="presentation">were determined <span dir="ltr" style="left: calc(var(–scale-factor)*515.74px); top: calc(var(–scale-factor)*403.13px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932477);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*416.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.853072);" role="presentation">be <span dir="ltr" style="left: calc(var(–scale-factor)*85.70px); top: calc(var(–scale-factor)*416.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96389);" role="presentation">163.9 mg/g and 77.5 mg/g <span dir="ltr" style="left: calc(var(–scale-factor)*202.13px); top: calc(var(–scale-factor)*416.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9735);" role="presentation">respectively at contact time of 55min <span dir="ltr" style="left: calc(var(–scale-factor)*363.31px); top: calc(var(–scale-factor)*416.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02036);" role="presentation">and pH of 2. <span dir="ltr" style="left: calc(var(–scale-factor)*422.74px); top: calc(var(–scale-factor)*416.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.982677);" role="presentation">Equilibrium, kinetic and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*429.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91907);" role="presentation">thermodynamic s<span dir="ltr" style="left: calc(var(–scale-factor)*142.58px); top: calc(var(–scale-factor)*429.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947527);" role="presentation">tudies further <span dir="ltr" style="left: calc(var(–scale-factor)*201.77px); top: calc(var(–scale-factor)*429.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973207);" role="presentation">revealed the suitability of MNPSD for use as a <span dir="ltr" style="left: calc(var(–scale-factor)*404.11px); top: calc(var(–scale-factor)*429.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949087);" role="presentation">cost effective<span dir="ltr" style="left: calc(var(–scale-factor)*459.22px); top: calc(var(–scale-factor)*429.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941601);" role="presentation">, environmental <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*442.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.983593);" role="presentation">friendly <span dir="ltr" style="left: calc(var(–scale-factor)*106.10px); top: calc(var(–scale-factor)*442.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901846);" role="presentation">adsorbent for <span dir="ltr" style="left: calc(var(–scale-factor)*161.78px); top: calc(var(–scale-factor)*442.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903024);" role="presentation">wastewater treatment especially for removal of hazardous pesticides.